PEMEROLEHAN BAHASA INGGRIS PADA ANAK DI TK ADVENT RAMA RATAHAN - RONDONUWU, OLIVIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study is an attempt to know the English language acquisition by children at TK Advent Rama in Ratahan. The objective of this study is to identify and analyze the English language acquisition by children at TK Advent Rama in Ratahan. A qualitative method was used with the support of simple statistical analysis answer research question, Tabors and Snow’s theory on telegraphic and formulaic speech and productive language was used in this research. The research took 17 students as samples and the data were taken through interviews. The outcome of the interviews shows that the students acquisition of English language vocabulary is in two stages (telegraphic/formulaic speech and productive language) as follows : parts of body (41% telegraphic, 59% productive), transportation (65% telegraphic, 35% productive), color (47% telegraphic, 53% productive), classroom (41% telegraphic, 59% productive), job (47% telegraphic, 53% productive), nation (47% telegraphic, 53% productive), universe (82% telegraphic, 18%productive) , self introduction (59% telegraphic, 41% productive), memory verse 100% productive language, prayer before studying 100% productive language, prayer eat 100% productive language and prayer after studying/going home 100% productive language. This research, then, recommends the teacher at TK Advent Rama in Ratahan to increase the students motivation in learning English and in practicing English more often. This research also suggests to conduct further research focusing on the students in preschool, kindergarten or elementary school to examine their English language acquisition. Key words : English Language Acquisition, Children and Kindergarten (TK)